2014
DOI: 10.5535/arm.2014.38.6.784
|View full text |Cite
|
Sign up to set email alerts
|

Age Specificity in General and Rehabilitation Medical Services in Children With Cerebral Palsy

Abstract: ObjectiveTo review the medical utilization in children with cerebral palsy according to age and discern particularitiesMethodsFrom January 2007 to December 2007, 10,659 children and adolescents between 1 and 18 years of age who had filed national insurance claims for a diagnosis of cerebral palsy were selected. Age was chosen as an independent variable, and the population was categorized into specific age groups to verify any differences in medical service utilization. Admission duration to rehabilitation, num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(26 reference statements)
0
4
1
Order By: Relevance
“…A study conducted in South Korea found that, unlike the findings of this study, neurodevelopmental therapy was the most frequently used intervention for adolescents with CP during rehabilitation (Kim, Hong, Lee, Lee, & Kang, 2014). This highlights that the content of rehabilitation provided to adolescents with CP is not consistent across the world.…”
Section: Discussioncontrasting
confidence: 43%
“…A study conducted in South Korea found that, unlike the findings of this study, neurodevelopmental therapy was the most frequently used intervention for adolescents with CP during rehabilitation (Kim, Hong, Lee, Lee, & Kang, 2014). This highlights that the content of rehabilitation provided to adolescents with CP is not consistent across the world.…”
Section: Discussioncontrasting
confidence: 43%
“…Future analyses might investigate the use of management options by age groups; for example, the use of physical therapy may dissipate after the early elementary years. 20 Since extent of ambulation can be considered roughly negatively correlated with severity, it is not surprising that the children considered to be likely nonambulatory had higher management option use, higher rates of care, and higher cost of care compared with those considered likely ambulatory. For example, utilization rates of antispasticity medications, including all forms of baclofen, were higher in nonambulatory children.…”
Section: Overall Likely Ambulatory Likely Nonambulatory Unknownmentioning
confidence: 99%
“…It is suggested that parents, and especially mothers of young children with disabilities, cut the number of hours they work in order to stay home with their infant with a disability, resulting in a possible increased financial burden on the family. Another study reported on the medical expenses for services among children with CP in South Korea (Kim et al, 2014). The authors indicated that the mean cost for general medical care in outpatient clinics was negatively associated with child's age, with medical costs for infants (1–2 years) and toddlers (3–6 years) significantly higher than those for school aged children or adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that parents, and especially mothers of young children with disabilities, cut the number of hours they work in order to stay home with their infant with a disability, resulting in a possible increased financial burden on the family. Another study reported on the medical expenses for services among children with CP in South Korea (Kim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%